The Effect of the Infographic Strategy on the Achievement and Developing of Historical Concepts among Second-grade middle school Students - Ibrahim Mohamed, Hanaa (International Journal of Psychosocial Rehabilitation, 2020)
The current research aims to find out the aftermath of the infographic strategy in attainment and the development of concepts among middle-class students by verifying the validity of the following zero hypotheses: 1- There is no statistically significant difference (0.05) between the average grades of female students in the experimental group studying Arab-Islamic history according to the infographic strategy and the average grades of female students in the same subject in the usual way in the distance learning test. 2- There is no statistically significant difference (0.05) between the average grades of female students in the experimental group studying Arabic-Islamic history according to the infographic strategy and the average grades of female students of the control group studying the same subject in the usual way in testing remote historical concepts. 3- There is no statistically significant difference (0.05) between the average grades of female students in the experimental group studying Arab-Islamic history according to a strategy infographic in the tribal and remote applications of the historical survey. 4- There is no statistically significant difference at the level of significance (0.05) between the average grades of female students of the control group studying the subject of Arab-Islamic history in accordance with the usual method in the tribal and remote applications to test historical concepts.